2021
DOI: 10.3390/ijerph18052583
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 Restrictions on Western Australian Children’s Physical Activity and Screen Time

Abstract: Physical activity is essential for children’s healthy development, yet COVID-19 physical distancing restrictions such as school closures and staying at home, playground closures, and the cancelling of organised community sport have dramatically altered children’s opportunities to be physically active. This study describes changes in levels of physical activity and screen time from February 2020 (i.e., before COVID-19 restrictions were introduced in Western Australia) to May 2020 (i.e., when COVID-19 restrictio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
81
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(90 citation statements)
references
References 31 publications
(30 reference statements)
5
81
0
4
Order By: Relevance
“…The correlation is that the reduced physical activity observed in the current study might have a negative impact of children's health. The results of the current study provide objective support to the findings of prior studies using parent-reported questionnaires that investigated the impact of the pandemic in children around the world and found physical activity to be significantly reduced by social distancing restrictions [6][7][8][9][10][11]45,46]. Evidence has already been reported regarding negative short-term health outcomes of the pandemic.…”
Section: Physical Activitysupporting
confidence: 86%
See 4 more Smart Citations
“…The correlation is that the reduced physical activity observed in the current study might have a negative impact of children's health. The results of the current study provide objective support to the findings of prior studies using parent-reported questionnaires that investigated the impact of the pandemic in children around the world and found physical activity to be significantly reduced by social distancing restrictions [6][7][8][9][10][11]45,46]. Evidence has already been reported regarding negative short-term health outcomes of the pandemic.…”
Section: Physical Activitysupporting
confidence: 86%
“…This study only included boys because it is a follow up of a previous study that only included boys. In terms of physical activity and sleep, some studies evaluating physical activity and sleep during the pandemic using questionnaires reported no significant differences between boys and girls in terms of the impact of the pandemic [6][7][8]10], although one did report a difference in physical activity [46]. Thus, it is hard to predict what the results would have been had we included girls.…”
Section: Limitationsmentioning
confidence: 96%
See 3 more Smart Citations